Half sandwich Ru(ii)-acylthiourea complexes: DNA/HSA-binding, anti-migration and cell death in a human breast tumor cell line. Issue 38 (18th September 2017) - Colina-Vegas, Legna; Luna-Dulcey, Liany; Plutín, Ana M.; Castellano, Eduardo E.; Cominetti, Marcia R.; Batista, Alzir A.
Abstract : Eight Ru(ii ) complexes were synthesized. The activities against MDA-MB-231 cells include anti-migration, arrest at the sub-G1 phase and cell death by apoptosis. Abstract : Organometallic ruthenium complexes as potential anticancer agents have been explored due to their suitable properties, such as stability in the solid state and in solution, water solubility and low toxicity. In this study, eight metal complexes of this class were synthesized, characterized and their important biological activities against a human breast tumor cell line (MDA-MB-231) were studied. Complexes1–8 were obtained in good yields and have been characterized by satisfactory elemental analyses, IR, 1D and 2D 1 H and 13 C 1 H NMR, UV-Vis spectroscopy, cyclic voltammetry, ESI-MS and X-ray diffractometry (1, 2, 3 and6 ). All complexes exhibit growth inhibition on human breast and lung tumor cell lines, with IC50 values ranging from 6.0 to 45.0 μM in 48 h. Four compounds were selected to evaluate the changes in the morphology, clonogenic, migration, cell cycle arrest and cell death in MDA-MB-231 cells. The complexes are able to induce morphological changes and inhibit the size, number of colonies and cell migration, and induce cell cycle arrest in the sub-G1 phase and apoptosis cell death. The interaction of the complexes with DNA was determined by performing spectroscopic titration, a competitive assay with thiazole orange, circular dichroism, gel electrophoresis and interactions with guanosine or guanosine monophosphate by 1 H NMR, indicating the non-covalent interaction. The HSA binding affinity measured by spectrophotometric titration, revealed the hydrophobic and spontaneous association with the human protein. Overall, the studies indicated that these metal complexes are potential agents against MDA-MB-231 cells, encouraging us to continue studies of these types of compounds.